Education and Fondness Study: Supplementary Food Provision of Depik (Rasbora tawarensis) and Tempe-Based Nugget Formulas to Toddler Mothers in Bener Mulie Village, Wih Pesam District, Bener Meriah Regency - Nafisah Salsabillah Syah Putri; Saiful Bakri (JAND: Journal of Applied Nutrition and Dietetic, 2022)
Efforts that support optimal growth and development for children will continue to be carried out. One way to overcome this is through the provision of supplementary feeding for toddlers at the Posyandu. This research aims to educate and test the preference for supplementary feeding nugget formula based on local food, depik fish (Rasbora tawarensis), and tempeh on mothers of stunting toddlers. This study used the quasi-experimental design research with dependent t-test and ANOVA test. The result showed that the average value of a mother’s knowledge before being educated was 42.50. Meanwhile, the average value after being educated is 52.00, meaning that there is an increase in knowledge after being educated. The results of the liking test showed that there were 2.5% of respondents who said they did not like it, 7.5% of respondents said they liked it somewhat, 57.5% of respondents said they liked it, and 32.5% of respondents said they really liked it. This shows that the supplementary feeding products of depik fish nuggets (Rasbora tawarensis) and tempeh are favored by mothers of toddlers. The results of the dependent t-test showed that the p-value was < 0.05 (0.006). Therefore, it can be concluded that education has a significant effect. Based on the results of the ANOVA test, which resulted in a p-value of < 0.05 (0.001), it was concluded that supplementary feeding nuggets based on local food, depik fish nuggets (Rasbora tawarensis), and tempeh are favored by mothers of toddlers. It is hoped that the relevant agencies can inform the public about supplementary feeding products and the manufacturing process that utilizes local food.